Use of DI-S and CPITN as predictors in dental caries studies in the primary dentition - Cleaton-Jones, P.; Hargreaves, J. A.; Beere, D.; et al. (My University, 1991)
The DI-S (simplified oral debris index), CPITN (Community Periodontal Index of Treatment Needs) and dmfs (dental caries experience in the primary dentition were recorded in 395 5-year-old black children living in rural and urban areas of Southern Africa. The DI-S and CPITN were grouped, independently and together, to examine their use as simple field methods of predicting dental caries. For each grouping the sensitivity, specificity and positive and negative predictor values were calculated. A CPITN grouping of 0 or of two or more sextants with bleeding, provided the most convenient specificity, sensitivity and predictor values. It is recommended that this simple method should now be used in prospective studies of caries activity.
PK
Keywords: Dental Caries/epidemiology; Oral Hygiene Index; Periodontal Index